Effective Pain Relief Interventions for Post-Hemorrhoidectomy Patients: A Rapid Evidence Review - Pujiyanti, Anindya Putri; Nurhamsyah, Donny; Anggriawan Ramadan, Angga; Syifatusolihah, Aulia; Rahma Hadi, Cantikya; Fitria Saputri, Melisa; Aulia Mujahidah, Shafira (STIKep PPNI Jawa Barat, 2025)
Background: Hemorrhoid disease, or piles, remains a prevalent global health issue. Hemorrhoidectomy is a common surgical intervention; however, effective postoperative pain management remains a persistent clinical challenge, directly influencing recovery outcomes and patient satisfaction. Objective: This rapid review aimed to identify the most effective nursing and clinical interventions for managing postoperative pain following hemorrhoidectomy. Methods: A rapid evidence review was conducted using five electronic databases: PubMed, ScienceDirect, Sage Journals, SpringerLink, and Scopus. The search included studies published between 2016 and 2024 that investigated pain management strategies for patients undergoing hemorrhoid surgery. Articles were screened based on predefined inclusion and exclusion criteria. A total of eight original research articles met the eligibility criteria and were included in the final analysis. Data on study design, sample size, intervention type, and pain outcomes were extracted and synthesized narratively. Results: Among the various interventions evaluated, the use of absorbable gelatin sponges as hemostatic agents demonstrated superior efficacy in reducing postoperative pain compared to other commonly used materials, such as epinephrine-soaked gauze. Six out of the eight included studies reported significant reductions in pain intensity and improved patient comfort with gelatin sponge application. These findings highlight the potential of this intervention as a cost-effective and clinically practical approach for enhancing postoperative care. Conclusion: Absorbable gelatin sponges represent a promising option for postoperative pain management following hemorrhoidectomy. Nonetheless, further large-scale and high-quality studies are warranted to strengthen the evidence base and inform broader clinical adoption